Zapomniane, wspomniane, zapomniane… - Rewers, Ewa (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The experience of reminiscences/dreams lies at the roots of the theory of individual and social memory. The author compares childhood remembrance-pictures of the two important events of 28 June 1956 in Poznań with documental photographs collected in the Museum of Poznań Uprising 1956. These traces-documents are apparently different in comparison with tablets fitted on the pavement leading to the Museum. Memory is plural, and there are three main levels of recognition, memory and forgetting discussed by the author.